2015
DOI: 10.1002/ece3.1833
|View full text |Cite
|
Sign up to set email alerts
|

Environmental controls on the distribution and diversity of lentic Chironomidae (Insecta: Diptera) across an altitudinal gradient in tropical South America

Abstract: To predict the response of aquatic ecosystems to future global climate change, data on the ecology and distribution of keystone groups in freshwater ecosystems are needed. In contrast to mid‐ and high‐latitude zones, such data are scarce across tropical South America (Neotropics). We present the distribution and diversity of chironomid species using surface sediments of 59 lakes from the Andes to the Amazon (0.1–17°S and 64–78°W) within the Neotropics. We assess the spatial variation in community assemblages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Our results seem to be consistent with the idea that the strong physical structuring of the study regions, with the distinct climatic and topographic conditions, override local environmental effects (partially supporting H1). Previous studies have also demonstrated the importance of macroscale descriptors over water chemistry in shaping aquatic community composition (diatoms and macroinvertebrates) in Arctic (Mykrä, Heino, & Muotka, ; Pajunen, Luoto, & Soininen, ; Vilmi, Karjalainen, & Heino, ), temperate (de Mendoza & Catalan, ) and tropical freshwaters (Matthews‐Bird et al., ; Steinitz‐Kannan et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Our results seem to be consistent with the idea that the strong physical structuring of the study regions, with the distinct climatic and topographic conditions, override local environmental effects (partially supporting H1). Previous studies have also demonstrated the importance of macroscale descriptors over water chemistry in shaping aquatic community composition (diatoms and macroinvertebrates) in Arctic (Mykrä, Heino, & Muotka, ; Pajunen, Luoto, & Soininen, ; Vilmi, Karjalainen, & Heino, ), temperate (de Mendoza & Catalan, ) and tropical freshwaters (Matthews‐Bird et al., ; Steinitz‐Kannan et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…However, where there is no direct evidence of human land use, such as cultigen pollen, distinguishing natural from anthropogenically induced burning and vegetation change can be difficult. In some cases anthropogenic deforestation and decreased moisture may result in similar signals in the pollen record, and therefore complementary proxies of past environmental change can be used to support interpretations, such as chironomids (Matthews-Bird et al, 2015;Williams et al, 2012) and geochemical records from speleothems.…”
Section: Indicators Of Human Land Use In 2 Kyr Pollen Recordsmentioning
confidence: 99%
“…. A.Flantua et al: Climate variability and human impact in South America during the last 2000 years cludes considering chironomids(Matthews-Bird et al, 2015;Williams et al, 2012), while indications of humans can come from non-pollen palynomorphs, such as the dung fungus Sporormiella(Williams et al, 2011).…”
mentioning
confidence: 99%
“…Compositional changing in chironomid assemblages along altitudinal gradients have been verified by many researchers worldwide (McKie et al 2005, Tejerina and Malizia 2012, Henriques-Oliveira and Nessimian 2010, Scheibler et al 2014, Robinson et al 2016, Matthews-Bird et al 2016). In mountain ecosystems the occurrence of chironomid species can be influenced by environmental changes related to altitude variation, such as temperature and oxygen availability (Oliver 1971, Pinder 1986, Eggermont and Heiri 2012), dispersal capacity (Ashe et al 1987), historical events (McKie et al 2005, Allegrucci et al 2006, Krosch et al 2011) or other regional particularities (Körner 2007).…”
Section: Discussionmentioning
confidence: 73%